O desencanto republicano e a reinterpretação da Independência - Nascimento, José Leonardo do (Revista USP, 2022)
The generation of Brazilian republicans was culturally formed by the philosophies of history of the various European scientificisms in the 19th century. It understood that the republican form of government corresponded, more than the monarchic one, to higher evolutionary stages. He believed that nations went through the same phases of historical evolution and that, therefore, the history of European nations prefigured the stages of Brazilian evolution. Knowing Brazil therefore presupposed comparing it with the history and social movements carried out by other nations. Some republicans sought to be guided by the French Revolution example and believed in the truly revolutionary character of the republican regime in Brazil. As the institutionalization of the regime denied their initial projects, “disillusioned”, they formulated numerous criticisms of the political forms instituted by the proclamation of the Republic and the Independence of Brazil.